2017
DOI: 10.1371/journal.pone.0174673
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fortified biscuits on micronutrient deficiencies among primary school children in Bangladesh

Abstract: BackgroundMicronutrient deficiencies can compromise the development potential of school-aged children, and their later health and productivity as adults. School feeding and school-based fortification approaches have been utilized globally to redress nutritional deficiencies in this age group.ObjectiveWe explored the acceptability and micronutrient impact of a Bangladesh Government supported school-based micronutrient fortification program for children attending rural primary schools in 10 disadvantaged sub-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…Many studies using vitamin D–fortified wheat or maize flour in LMICs support the use of these foods as a vehicle for increasing vitamin D intake. For example, biscuits made from multinutrient‐fortified wheat flour, which included vitamin D, fed to Bangladeshi school children significantly reduced the risk of vitamin D deficiency and other nutrient deficiencies relative to a control group . One of the few examples of a national wheat flour fortification initiative that includes vitamin D is the Jordanian wheat flour fortification program, introduced in 2009, which mandates vitamin D fortification at the level of 550 IU/kg (13.75 μg/kg) or approximately 58 IU vitamin D/serving (1.45 μg vitamin D/serving) .…”
Section: Interventions To Reduce the Prevalence Of Vitamin D Deficienmentioning
confidence: 99%
“…Many studies using vitamin D–fortified wheat or maize flour in LMICs support the use of these foods as a vehicle for increasing vitamin D intake. For example, biscuits made from multinutrient‐fortified wheat flour, which included vitamin D, fed to Bangladeshi school children significantly reduced the risk of vitamin D deficiency and other nutrient deficiencies relative to a control group . One of the few examples of a national wheat flour fortification initiative that includes vitamin D is the Jordanian wheat flour fortification program, introduced in 2009, which mandates vitamin D fortification at the level of 550 IU/kg (13.75 μg/kg) or approximately 58 IU vitamin D/serving (1.45 μg vitamin D/serving) .…”
Section: Interventions To Reduce the Prevalence Of Vitamin D Deficienmentioning
confidence: 99%
“…Several other similar studies by Mahfuz et al (20) (22). Other study by Adams et al In Banglades show fortified biscuits had a significant positive impact on mean levels of iron, folic acid, vitamin B12, retinol and vitamin D in primary school children (23). Study in China by Zhang et al Study in China showed Community-based complementary food supplements combined with dietary counselling can improve feeding practices and reduce anaemia prevalence in 6-23 mo old (24).…”
Section: S388mentioning
confidence: 88%
“…The fortification concentrations modeled were based on randomized trials in which increased concentrations of biological markers of micronutrient status were observed in participants fed fortified biscuits compared with control ( 22 , 35 – 37 ) ( Table 1 ). We also modeled fortification concentrations higher than those used in these studies under the assumption that such concentrations would also be technically feasible and would not cause adverse organoleptic profiles.…”
Section: Methodsmentioning
confidence: 99%